Effect of Thinking Aloud Pair Problem Solving (TAPPS) Method with Audio Visual Media for Students' Critical Thinking Ability - Ruly Anggraeni; Siska Andriani; Yahya AD (SAINTIS Publishing, 2019)
The study aimed to find out the effect of the Thinking Aloud Pair Problem Solving (TAPPS) learning method with Audio-visual media, Thinking Aloud Pair Problem Solving (TAPPS) learning methods and expository learning models on students' critical thinking skills conducted by researchers at the VIII SMP Middle School Bandar Lampung students. The method used in this study is a quantitative method with a type of quasi-experimental design. The population in this study were all eighth grade students of Bandar Bandar Junior High School and the samples were students of class VIII C, VIII D, VIII E. Class VIII C and VIII D as the experimental class and class VIII E as the control class. Data collection uses tests, observation, documentation and interviews. The data analysis technique used is the normality test, homogeneity test, hypothesis testing using one-way analysis ANOVA. Calculation of data was analyzed using inferential statistics with the help of SPSS 16.0 software application. Based on the results of the calculation of research data obtained that the value of sig α, α = 0.05 where the significance value of 0.049 H0 is rejected. Shows that the Thinking Aloud Pair Problem Solving (TAPPS) method with Audio-visual media is more effective than learning using the expository model on students' critical thinking abilities.